Ambient PM2.5 air pollution exposure and hepatocellular carcinoma incidence in the United States. - VoPham, Trang; Bertrand, Kimberly A.; Tamimi, Rulla M.; Laden, Francine; Hart, Jaime E. (Cancer Causes & Control, 2018)
Purpose: To conduct the first epidemiologic study prospectively examining the association between particulate matter air pollution < 2.5 µm in diameter (PM2.5) exposure and hepatocellular carcinoma (HCC) risk in the U.S.Methods: Surveillance, Epidemiology, and End Results (SEER) provided information on HCC cases diagnosed between 2000 and 2014 from 16 population-based cancer registries across the U.S. Ambient PM2.5 exposure was estimated by linking the SEER county with a spatial PM2.5 model using a geographic information system. Poisson regression with robust variance estimation was used to calculate incidence rate ratios and 95% confidence intervals (CIs) for the association between ambient PM2.5 exposure per 10 µg/m3 increase and HCC risk adjusting for individual-level age at diagnosis, sex, race, year of diagnosis, SEER registry, and county-level information on health conditions, lifestyle, demographic, socioeconomic, and environmental factors.Results: Higher levels of ambient PM2.5 exposure were associated with a statistically significant increased risk for HCC (n = 56,245 cases; adjusted IRR per 10 µg/m3 increase = 1.26, 95% CI 1.08, 1.47; p < 0.01).Conclusions: If confirmed in studies with individual-level PM2.5 exposure and risk factor information, these results suggest that ambient PM2.5 exposure may be a risk factor for HCC in the U.S.